A NAC gene regulating senescence improves grain protein, Zn, and Fe content in wheat - Uauy, Cristobal (Science, 2006)
Enhancing the nutritional value of food crops is a means for improving human nutrition and health. We report here the positional cloning of Gpc-B1, a wheat quantitative trait locus associated with increased grain protein, Zn, and Fe content. The ancestral wild wheat allele encodes a NAC transcription factor (NAM-B1) that accelerates senescence and increases nutrient remobilization from leaves to developing grains, whereas modern wheat varieties carry a non-functional NAM-B1 allele. Reduction in RNA levels of the multiple NAM homologs by RNA interference delayed senescence by over three weeks and reduced wheat grain protein, Zn, and Fe content by over 30%.